2020
DOI: 10.1042/bsr20200830
|View full text |Cite
|
Sign up to set email alerts
|

From sepsis to acute respiratory distress syndrome (ARDS): emerging preventive strategies based on molecular and genetic researches

Abstract: A healthy body activates the immune response to target invading pathogens (i.e. viruses, bacteria, fungi, and parasites) and avoid further systemic infection. The activation of immunological mechanisms includes several components of the immune system, such as innate and acquired immunity. Once any component of the immune response to infections is aberrantly altered or dysregulated, resulting in a failure to clear infection, sepsis will develop through a pro-inflammatory immunological mechanism. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 61 publications
(70 reference statements)
0
46
0
3
Order By: Relevance
“… 18 , 19 The increased productions of some inflammatory agents can contribute to ARDS in patients, including C-reactive protein (CRP), IL-1β, IL-1α, IL-6, and TNF-α. 11 , 20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 , 19 The increased productions of some inflammatory agents can contribute to ARDS in patients, including C-reactive protein (CRP), IL-1β, IL-1α, IL-6, and TNF-α. 11 , 20 …”
Section: Introductionmentioning
confidence: 99%
“… 21 In addition, these studies have shown that the increased frequencies of Th1 and CD8+ T cells in patients with MERS-CoV infection were correlated to the good prognosis of the disease, whereas Th2 cytokines were associated with higher mortality. 20 , 21 Others have revealed that Th1 and Th17 cells can stimulate and participate in inducing inflammatory reactions in patients with COVID-19. 19 Another immune cell associated with pathogenesis of COVID-19 may be regulatory T cells (Tregs), the immune regulatory cells critical for inhibiting inflammation and immune response-associated tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…ARDS is a serious life-threatening condition, which integrates with acute onset of sepsis, pneumonia and severe trauma. 25 In 2019, a newly emerged novel corona virus strain SARS-CoV-2 evidenced a wreaking ARDS case in 67%-85% of critically ill patients with 61.5% mortality. 26 Although the pathogenesis is much evolved, still there is no specific pharmacologic treatment that has been identified to manage ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…The CD4 + T helper (Th) cells have a remark role in the function of coronaviruses through the interaction with Tregs [27] . Previous studies on MERS-CoV patients, a disease with similar pathogenesis to COVID-19, have shown that the number of Th1 was associated with the good prognosis of the disease, but Th2 cytokines were related to the high rate of death [17] , [28] . Furthermore, Th17, as another subset of CD4 + T helper cells, can participate in the cytokine storm in ARS-CoV-2 and probably enhance pulmonary edema [29] .…”
Section: Introductionmentioning
confidence: 94%
“…It is reported that in the great numbers of severe cases, there were the increased productions of some immune factors such as TNFα, IL-2R, IL-6, and IL-10 [14] . Moreover, it is documented that the increased levels of C-reactive protein (CRP), IL-1α, IL-1β, IL-6, and TNF-α can participate in ARDS in these patients [11] , [17] . Previous studies have revealed that peripheral level of the natural killer cell (NK cell) was significantly decreased in the severe stage of the disease compared to the mild disease stage, but it is unknown whether this reduction was due to cell death and/or cell accumulation in the infected tissues [18] , [19] .…”
Section: Introductionmentioning
confidence: 99%